2015
DOI: 10.1590/s0102-865020150120000010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Low-Level Laser Therapy (LLLT) in the process of healing diabetic foot ulcers

Abstract: PURPOSE:To evaluate the effects of the low-level laser therapy applying Laser on the tissue repair in ulcer carriers due to diabetes. METHODS:Sixteen type II diabetic patients, ulcer carriers in the lower limbs, participated in the research from which eight were in the control group and eight were submitted to the low-level laser therapy with a pulsed wave form, visible ray, wave length of 632.8 nm, mW peak power, (Laser -HTM). The application time was of 80 (4J/cm2 ) seconds. The application was punctual with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 13 publications
2
55
0
17
Order By: Relevance
“…The previous reviews found nine studies of physical therapies, including shockwaves, ultrasound, laser therapy, magnetism, and electrical current. The current review found a number of new controlled studies; one study of ultrasound two of extracorporeal shockwaves, three of low level Laser therapy, one of advanced class IV laser emitting four wavelengths, two using photodynamic therapy (PDT), one using infrared radiation, and one on pneumatic compression . All were of high risk of bias or showed no evidence of benefit.…”
Section: Recommendationsmentioning
confidence: 99%
“…The previous reviews found nine studies of physical therapies, including shockwaves, ultrasound, laser therapy, magnetism, and electrical current. The current review found a number of new controlled studies; one study of ultrasound two of extracorporeal shockwaves, three of low level Laser therapy, one of advanced class IV laser emitting four wavelengths, two using photodynamic therapy (PDT), one using infrared radiation, and one on pneumatic compression . All were of high risk of bias or showed no evidence of benefit.…”
Section: Recommendationsmentioning
confidence: 99%
“…The antibacterial role of PBMT has been investigated, utilizing an approach known as photodynamic antimicrobial therapy or lethal photosensitization 15 . In this treatment, the light emitted by a PBMT activates a specific photosensitizer triggering biochemical changes capable of killing bacteria 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…91 The RCTs exploring the efficacy of laser therapy on wound healing are few, have small sample sizes, and show variable results. [92][93][94] Phototherapy. Phototherapy causes photochemical reactions that lead to a rapid increase in cellular metabolic activity and cell growth, vasodilation, and angiogenesis, which can result in faster wound healing.…”
mentioning
confidence: 99%